The Effectiveness of Murabahah Financing System in Increasing Profitability of Islamic Banks in Indonesia - Haris, Muhammad Haris; Najwa, Najwa Shifa Qursya (Cattleya Darmaya Fortuna, 2023)
This study aims to analyze the effectiveness of the murabahah financing system in increasing the profitability of Islamic banks in Indonesia. The murabahah financing system is considered as an alternative financing that is in accordance with Islamic principles, which provides benefits for both banks and customers. The analysis was conducted by evaluating several aspects, including bank profitability, financing performance, associated risks, impact on customer satisfaction, and external factors that influence it. The results of the study indicate that the murabahah system is effective in increasing the profitability of Islamic banks, with significant profit margins and high customer satisfaction. However, challenges related to financing risks such as default and fluctuations in the price of goods need to be managed carefully. This study provides insight into how the murabahah financing system can continue to develop in the Islamic banking sector in Indonesia.